Development Finance Via Diaspora Bonds Track Record And Potential - Ketkar, Suhas L. (The World Bank, 2007)
A diaspora bond is a debt instrument issued by a country - or potentially, a sub-sovereign entity or a private corporation - to raise financing from its overseas diaspora. Israel and India have raised